Effect of transcranial magnetic stimulation on electroencephalogram activity and emotions - Al-Amoodi, Waleed Hussein Ahmed Bawjeh (2019)
Transcranial magnetic stimulation (TMS) is one of the current approach to stimulate the neurons in the brain, by changing the magnetic fields in that area using electromagnetic induction, neurons with weak signals amplified. Many studies showing that this stimulation can enhance the brain activity, therefore it became one of the trending approaches to study the brain conductivity and excitability, in term of safety many studies has shown that this type of stimulation can be applied with no risk of side effect in normal subjects. In the meantime, there are many theories and many studies about thoughts and physiological behaviour and the origin of emotions and it is agreed to be the brain, and the efficiency of integrating transcranial magnetic stimulation to the brain activity and emotions remains not clearly established. The main objective of this project is to evaluate the effect of transcranial magnetic stimulation of healthy subjects to electroencephalogram (EEG) in response to emotions. Therefore, in this research, sixteen subjects exposed to visual stimulus to induce their emotions is carried out, these emotions measured by using electroencephalogram (EEG) recorder, and the signal amplified by applying transcranial magnetic stimulation (TMS). After that, the data has been recorded and multiple filtering techniques has been applied to filter out the noises, and then followed by feature extraction method to extract the statistical information from the signal using power spectral density, and finally the results classified by using LDA and kNN classifiers. The results of this study showed that transcranial magnetic stimulation could enhance the brain signal and amplify the emotion intensity. Morover, it also help improve the classification accuracy of emotions and the highest emotion effect was afraid 79% using LDA classifier and followed by happy emotion 67% using kNN classifier, and overall classification improved the results also shows that the temporal and occipital lobe mainly invloves in emotion which support previous studies outcome.